Disaster Preparedness Communication for Residents at Kalibata City Apartment - Wibowo, Teguh; Nugrahajati, Susilastuti Dwi; Paripurno, Eko Teguh (Jurnal Paradigma, 2024)
The construction of vertical housing or apartments is one of the government's efforts to meet the increasing residential needs of urban communities. The hazards that haunt a housing area such as the occurrence of unit fires, the feeling of earthquakes to other events will cause potential disasters and pose a risk. Residents have the right to live in a safe and comfortable residence, of course, with the obligation of the building manager to be able to facilitate these conditions. Effective communication is an important part of receiving messages and information that suits the needs of residents in understanding the risks that exist. The research was conducted to see the ways of communication carried out by residents who live in Kalibata City apartments as a form of disaster preparedness. The method of observation and direct involvement in forums in the Kalibata City resident community was carried out by combining literature review from previous documents. The result of the research is a communication method found in a community in a vertical residential area that matches the character of urban society.